Methodological Strategies to put into operation a Transdisciplinary Educational Practice in collaboration with the University Members, in the Baccalaureates of Centro de Estudios Universitarios Arkos (CEUArkos), Puerto Vallarta, Jalisco, Mexico - Espinosa Martínez, Ana Cecilia (2011)
This paper summarizes the processes experienced and results obtained throughout a research-action carried out with professors, students and directors of the different areas of CEUArkos, a university center located in Puerto Vallarta, Jalisco, México. Its purpose is building and taking into practice methodological strategies to put into operation transdisciplinarity and complexity in learning, teaching and research –as part of teaching– in all its baccalaureates, to set the wheels in motion for university education to move from disciplinarity to transdisciplinarity in all the study programs. The university curriculum is also analyzed in this paper.